Quantitative changes in cytological molecular markers during primary medical treatment of breast cancer: A pilot study - Makris, A.; Powles, T.J.; Allred, D.C.; Ashley, S.E.; Trott, P.A.; Ormerod, M.G.; Dowsett, M. (Breast cancer research and treatment, 1999)
To quantify the changes in biological molecular markers during primary medical treatment in patients with operable breast cancer and to assess their possible relationship with response to treatment. The treatment group consisted of 31 patients with operable breast carcinomas, median age 57 years (range 41-67), treated with four 3-weekly cycles of chemotherapy with Mitoxantrone, methotrexate (+/- mitomycin C), and tamoxifen before surgery. Fine needle aspiration (FNA) was used to obtain samples from patients prior to and at 10 or 21 days post-treatment. The following molecular markers were assessed: estrogen receptor (ER), progesterone receptor (PgR), p53, Bcl-2, and Ki67 measured by immunocytochemistry, and ploidy and S-phase fraction (SPF) by flow cytometry. To evaluate the reproducibility of the technique, repeat FNA was performed in a separate non-treatment control group of 20 patients and the same molecular markers assessed, two weeks after the first sample with no intervening treatment. The non-treatment control group showed a high reproducibility for the measurement of molecular markers from repeat FNA. In the treatment group there was a non-significant reduction in SPF and a significant reduction (p = 0.005) in Ki67. Patients who responded to neoadjuvant therapy were more likely to have a reduction in these two markers than those who failed to respond. Similarly, a reduction in ER scores was observed between the first and second samples (p = 0.04). For PgR, the change between the first and second samples was not significant although there was a significant difference between responders and non-responders (p = 0.03). All nine patients with an increase in PgR were responders. No significant changes in p53 or Bcl-2 were observed during treatment. Molecular markers can be adequately measured from FNA samples prior to and during neoadjuvant therapy. Changes in cellular proliferation and hormone receptors have been shown that may be related to tumour response. These relationships should be assessed in a larger cohort of patients.